Deepening Local Democracy in Latin America : Participation, Decentralization, and the Left - Goldfrank, Benjamin (Book collections on Project MUSE., 2011)
"Addresses the question of why institutions meant to attract citizen participation succeed in strengthening civil society and improving state responsiveness and transparency in some places, but fail in others. Focuses on urban politics in Porto Alegre (Brazil), Montevideo (Uruguay), and Caracas (Venezuela)"--Provided by publisher.